STRATEGI PENINGKATAN DAYA TARIK PENGUNJUNG WISATA OLEH DINAS KETAHANAN PANGAN DAN PERTANIAN KOTA SURABAYA (STUDI PADA PENGEMBANGAN KEBUN RAYA MANGROVE GUNUNG ANYAR) - Salsabila, Faza Saila; Eprilianto, Deby Febriyan (Publika, 2024)
The development of the Gunung Anyar Mangrove Botanical Garden in the city of Surabaya is an important step in promoting sustainable mangrove management and supporting the achievement of the 2045 SDGs goals. The fact that mangrove governance development still receives less attention shows the need for further research. This study aims to describe the increase in tourist attraction in the development of the Gunung Anyar Mangrove Botanical Garden. The theory of tourism development by Amerta (2019) is used as a basis for building research arguments. The research method used is qualitative descriptive. Data was collected through observation, documentation, interviews, and secondary data analysis. The research subjects involved 11 people consisting of managers and visitors. The results of the study show that the development of botanical gardens includes: (1) Attraction, realized through increasing plant collections, adding attractions, interesting activities and tour packages; (2) Amenities, realized through environmentally friendly and disability-friendly facilities such as jogging tracks, many garbage cans, the availability of gazebos, clean toilets; (3) Access, realized through the existence of adequate parking lots, directions, mobilization with buggy cars, free wifi, and clear marketing information; (4) Ancillary, realized through training, coaching, monitoring, evaluation and cooperation with local communities, private parties, universities and all OPDs in the city of Surabaya. Despite obstacles such as lack of community participation, narrow road access, limited capacity of toilets and prayer rooms, lack of public transportation and the need for training in human resources, the development carried out can be said to be quite successful, competitive, and able to increase visitor attraction and the sustainability of mangrove management at the Gunung Anyar Mangrove Botanical Garden. This research is limited to one location, but this research opens up further research opportunities to expand the scope of the research.